The Quality Implementation Framework: A Synthesis of Critical Steps in the Implementation Process - Meyers, Duncan C.; Durlak, Joseph A.; Wandersman, Abraham (American journal of community psychology, 2012)
Implementation science is growing in importance among funders, researchers, and practitioners as an approach to bridging the gap between science and practice. We addressed three goals to contribute to the understanding of the complex and dynamic nature of implementation. Our first goal was to provide a conceptual overview of the process of implementation by synthesizing information from 25 implementation frameworks. The synthesis extends prior work by focusing on specific actions (i.e., the “how to”) that can be employed to foster high quality implementation. The synthesis identified 14 critical steps that were used to construct the Quality Implementation Framework (QIF). These steps comprise four QIF phases: Initial Considerations Regarding the Host Setting, Creating a Structure for Implementation, Ongoing Structure Once Implementation Begins, and Improving Future Applications. Our second goal was to summarize research support for each of the 14 QIF steps and to offer suggestions to direct future research efforts. Our third goal was to outline practical implications of our findings for improving future implementation efforts in the world of practice. The QIF’s critical steps can serve as a useful blueprint for future research and practice. Applying the collective guidance synthesized by the QIF to the Interactive Systems Framework for Dissemination and Implementation (ISF) emphasizes that accountability for quality implementation does not rest with the practitioner Delivery System alone. Instead, all three ISF systems are mutually accountable for quality implementation.